Migration, income redistribution, and international capital mobility - Jürgen Meckl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
This paper studies income-redistribution effects from labor migration in a small open economy under alternative assumptions on the international mobility of capital. Our principal result is that induced international capital flows dampen or may even reverse redistribution effects. However, as long as the location of capital is unaffected by migration redistribntion effects may be greater if some of the capital is foreign owned, depending on whether labor and capital are friends or enemies. Only then national redistribution of income is accompanied by international redistribution effects.
Keywords: 330; factor mobility; income distribution; international trade; Arbeitsmigranten; Einkommensumverteilung; Kapitalmobilität; Theorie